THE ANALYSIS OF RISK FACTORS FOR COMPLIANCE WITH CONSUMPTION OF BLOOD SUPPLEMENTING TABLETS IN ADOLESCENT WOMEN AT SMA NEGERI 5 KUPANG - Allo, Ariani Alfonsina; Helga J. N Ndun; Mega O. L. Liufeto (Medika Alkhairaat: Jurnal Penelitian Kedokteran dan Kesehatan, 2024)
Anaemia is a condition in which the number of red blood cells or the haemoglobin concentration within them is lower than normal. High incidence of anemia in adolescent girls is because there are still many adolescent girls who are not accustomed to consuming iron supplement. The purpose of this study was to determine the risk factors for compliance with iron supplementation consumption among adolescent girls at SMA Negeri 5 Kupang. This was an quantitative study with case-control design. There was total of 64 respondents in this study which consisted of 32 case groups and 32 control groups. The independent variables in this study were knowledge, attitude, iron supplement availability, family support and peer support and the dependent variable was iron supplement consumption compliance. It was then analyzed using Chi Square test and Odds Ratio (OR). It was found that there was an association between knowledge (OR=5.0; CI 95%=1.721-14.705), attitude (OR=3.6; CI 95%=1.292-10.263), family support (OR=5.7; CI 95%=1.868-14.703) and peer support (OR=3.1; CI 95%=1.676-14.025) with TTD consumption compliance. Meanwhile, there was no association between iron supplement availability (p-value 0.060) with iron supplement consumption compliance. Schools need to establish programs related to anemia to help students adhere to taking iron supplement.